Results from an interlaboratory comparison of areal surface texture parameter extraction from X-ray computed tomography of additively manufactured parts - Townsend, Andrew; Racasan, Radu; Bills, Paul; Thompson, Adam; Senin, Nicola; Leach, Richard K.; Blunt, Liam (2017)
This paper presents the results of the CT-STARR (CT-Surface Texture for Additive Round Robin) interlaboratory comparison. The study compares the results obtained for the extraction of areal surface texture data per ISO 25178-2 from five X-ray computed tomography (XCT) volume measurements from each of four laboratories. To reduce the number of process variables, all participants utilise a Nikon XCT machine, either an XT H 225 industrial CT or an MCT225 metrology CT. Measurement process parameters, such as physical X-ray filtering, acceleration voltage and filament current, are set at similar values for all machines. All data processing and computation to extract, align, crop, filter and generate surface texture parameter information and deviation analysis results from the measurement volumes is performed by one participant. Two Ti6Al4V ELI (extra low interstitial) components are included in each of the XCT acquisitions. The first component is an additively manufactured cube built on an Arcam Q10 electron beam melting machine. Surface texture data is extracted from XCT scans of this part. The second component is a machined artefact designed for XCT scaling and surface determination analysis and verification. The data extracted from XCT measurements of these components is compared with measurements from coordinate measuring machine, focus variation and stylus instruments. The effect of scaling correction and XCT surface determination on extracted surface texture data, as well as measurement repeatability and reproducibility, are discussed.